FX knockout CHO hosts can express desired ratios of fucosylated or afucosylated antibodies with high titers and comparable product quality. Issue 3 (4th October 2016) - Louie, Salina; Haley, Benjamin; Marshall, Brett; Heidersbach, Amy; Yim, Mandy; Brozynski, Martina; Tang, Danming; Lam, Cynthia; Petryniak, Bronislawa; Shaw, David; Shim, Jeongsup; Miller, Aaron; et al.
ABSTRACT: During antibody dependent cell cytotoxicity (ADCC) the target cells are killed by monocytes and natural killer cells. ADCC is enhanced when the antibody heavy chain's core N‐linked glycan lacks the fucose molecule(s). Several strategies have been utilized to generate fully afucosylated antibodies. A commonly used and efficient approach has been knocking out the FUT8 gene of the Chinese hamster ovary (CHO) host cells, which results in expression of antibody molecules with fully afucosylated glycans. However, a major drawback of the FUT8‐KO host is the requirement for undertaking two separate cell line development (CLD) efforts in order to obtain both primarily fucosylated and fully afucosylated antibody species for comparative studies in vitro and in vivo. Even more challenging is obtaining primarily fucosylated and FUT8‐KO clones with similar enough product quality attributes to ensure that any observed ADCC advantage(s) can be strictly attributed to afucosylation. Here, we report generation and use of a FX knockout (FXKO) CHO host cell line that is capable of expressing antibody molecules with either primarily fucosylated or fully afucosylated glycan profiles with otherwise similar product quality attributes, depending on addition of fucose to the cell culture media. Hence, the FXKO host not only obviates the requirement for undertaking two separate CLD efforts, but it also averts the need for screening many colonies to identify clones with comparable product qualities. Finally, FXKO clones can express antibodies with the desired ratio of primarily fucosylated to afucosylated glycans when fucose is titrated into the production media, to allow achieving intended levels of FcγRIII‐binding and ADCC for an antibody. Biotechnol. Bioeng. 2017;114: 632–644. © 2016 Wiley Periodicals, Inc. Abstract : FX knock out CHO host cell lines enable expression of fucosylated or afucosylated antibodies, or even desired ratios of antibodies with such glycan modifications simply by titrating fucose into the media. Since the same cell line can express both versions of the antibody, titer and product quality attributes remain comparable. This feature may be helpful in tuning the ADCC response by either natural killer and/or polymorphonuclear cells.